The serum soluble scavenger with 5 domains levels: A novel biomarker for individuals with heart failure - Ge, Yulong; Liu, Xiaoqiang; Chen, Hangwei; Li, Gonghao; Xing, Xing; Liu, Junyi; Zhang, Chunxia; Zhuge, Ying; Wang, Fang (Frontiers in Physiology, 2023)
Background: We aimed to explore the relationship between the serum Soluble Scavenger with 5 Domains (SSC5D) levels and heart failure (HF). Methods and Results: We retrospectively enrolled 276 patients diagnosed with HF or normal during hospitalization in Shanghai General Hospital between September 2020 and December 2021. Previously published RNA sequencing data were re-analyzed to confirm the expression profile of SSC5D in failing and non-failing human and mouse heart tissues. Quantitative real-time polymerase chain reaction assay was used to quantify Ssc5d mRNA levels in murine heart tissue after myocardial infarction and transverse aortic constriction surgery. To understand the HF-induced secreted proteins profile, 1,755 secreted proteins were investigated using human dilated cardiomyopathy RNA-seq data, and the results indicated that SSC5D levels were significantly elevated in failing hearts compared to the nonfailing. Using single-cell RNA sequencing data, we demonstrated that Ssc5d is predominantly expressed in cardiac fibroblasts. In a murine model of myocardial infarction or transverse aortic constriction, Ssc5d mRNA levels were markedly increased compared with those in the sham group. Similarly, serum SSC5D levels were considerably elevated in the HF group compared with the control group [15789.35 (10745.32-23110.65) pg/ml, 95% CI, (16263.01-19655.43) vs 8938.72 (6154.97-12778.81) pg/ml, 95% CI, (9337.50-11142.93); p<0.0001]. Moreover, serum SSC5D levels were positively correlated with N-terminal pro-B-type natriuretic peptide (R=0.4, p=7.9e-12) and inversely correlated with left ventricular ejection fraction (R=-0.46, p=9.8e-16). Conclusion: We concluded that SSC5D was a specific response to HF. Serum SSC5D may function as a novel biomarker and therapeutic target for patients with HF.